Management of Interactive Flat Panel (IFP) utilization to enhance learning quality in junior high schools: A comparative study at SMPN 1 Bojongsoang and SMPN 1 Dayeuhkolot - Eva Dianawati Wasliman; Muhammad Andriana Gaffar; Saofanita; Fitria Sukmawati Kusnadi (Privietlab, 2026)
This study aims to examine the management of Interactive Flat Panel (IFP) utilization as a strategy for enhancing the quality of learning in junior high schools. A qualitative approach employing a case study method was adopted at SMPN 1 Bojongsoang and SMPN 1 Dayeuhkolot, both of which have implemented IFP in their learning processes. Data were collected through observations and document analysis. The findings reveal that the management of IFP utilization in both schools has been implemented effectively and has contributed positively to improving learning quality, particularly in increasing student engagement and strengthening students’ digital literacy competencies. The use of IFP has enabled more interactive, student-centered, and technology-enhanced learning experiences. However, the optimization of IFP utilization still requires greater support in terms of infrastructure development and the continuous enhancement of teachers’ digital competencies. Therefore, this study recommends the implementation of sustainable professional development programs and the strengthening of school management practices in managing IFP utilization, thereby maximizing the digitalization of learning and supporting the improvement of educational quality in the twenty-first century.